Aldehydes and ketones in pyrolysis oil: analytical determination and their role in the aging process. Issue 12 (4th March 2022) - Baehr, Clarissa; Smith, Gavin J.; Sleeman, Daniel; Zevaco, Thomas A.; Raffelt, Klaus; Dahmen, Nicolaus
Abstract : A chemical-analytical procedure by 1 H-NMR was developed to determine the total concentration of aldehydes in a hardwood-based pyrolysis oil during the process of accelerated aging at 80 °C for 48 h. It is compared to results of carbonyl titration. Abstract : Aldehydes and ketones are known to play a role in the aging process of pyrolysis oil and generally, aldehydes are known for their high reactivity. In order to discern in pyrolysis oil the total aldehyde concentration from that of the ketones, a procedure for the quantification of aldehydes by 1 H-NMR was developed. Its capability is demonstrated with a hardwood pyrolysis oil at different stages of the aging process. It was treated by the Accelerated Aging Test at 80 °C for durations of up to 48 h. The aldehyde concentration was complemented by the total concentration of carbonyls, quantified by carbonyl titration. The measurements show, that the examined hardwood pyrolysis oil contained 0.31–0.40 mmol g −1 aldehydes and 4.36–4.45 mmol g −1 ketones. During the first 24 h, the aldehyde concentration declined by 23–39% and the ketone concentration by 9%. The rate of decline of aldehyde concentration slows down within 24 h but is still measureable. In contrast, the total carbonyl content does not change significantly after an initial decline within the first 4 h. Changes for vinylic, acetalic, phenolic and hydroxyl protons and for protons in the α -position to hydroxy, ether, acetalic and ester groups were detected, by 1 H-NMR. In the context of characterizing pyrolysis oil and monitoring the aging process, 1 H-NMR is a reliable tool to assess the total concentration of aldehydes. It confirms the reactivity of aldehydes and ketones and indicates their contribution to the instability of pyrolysis oil.